THE EFFECT OF RECRUITMENT AND JOB PLACEMENT ON EMPLOYEE PRODUCTIVITY AT PT. DEWASUTRATEX CIMAHI - Akmad Baidun; Henny Herawati; Ariraya Sulistya Sedayu; Eka Kurnia Saputra (Pusat Riset dan Inovasi Nasional, 2023)
The success or failure of an organization in achieving its predetermined goals is highly dependent on the ability of its human resources (employees) to carry out the tasks or work assigned to them. This study aims to determine the effect of recruitment and work placement on employee productivity at PT. Dewasutratex Cimahi. The data processing method is carried out using a saturated sampling approach, namely the sampling method in which the entire population is used as a research sample totaling 46 employees. Data analysis was carried out using validity and reliability tests, normality tests, classic assumption tests, simple linear regression tests, determination tests, F tests and T tests. Based on the results of the study, it can be concluded that Recruitment and Job Placement partially have a significant effect on Work Productivity at PT. Dewasutratex Cimahi. The effect of recruitment on work productivity is 83.6% and the remaining 16.4 is influenced by other variables outside the research. While the effect of placement on work productivity is 87.6% and the remaining 12.4 is influenced by other variables.